2008
DOI: 10.1002/sia.2650
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the angular distribution of the surface excitation parameter for Ti, Fe, Cu, Pd, Ag, and Au

Abstract: We define surface excitation parameter (SEP) as the change in excitation probability of an electron caused by the presence of the surface in comparison with an infinite medium, and we calculate the angular dependence of the SEP for different metals (Ti, Fe, Cu, Pd, Ag, and Au), for angles to the surface normal between 10• and 70• and for different energies. The calculations are based on a study of energy-differential inelastic electron scattering cross-sections obtained from the software Quantitative analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Calculations were performed within a dielectric response theory [26] by means of the QUEELS-ε(k, ω)-REELS software. [24] We have found that SEP for polymers are, in general, smaller than those obtained for metals, [21,22] and we ascribe this to the band gap which reduces the relative importance of surface excitations. These results are in agreement with previous calculations [23] achieved for oxides, which are also characterized by the presence of a band gap.…”
Section: Resultsmentioning
confidence: 84%
“…Calculations were performed within a dielectric response theory [26] by means of the QUEELS-ε(k, ω)-REELS software. [24] We have found that SEP for polymers are, in general, smaller than those obtained for metals, [21,22] and we ascribe this to the band gap which reduces the relative importance of surface excitations. These results are in agreement with previous calculations [23] achieved for oxides, which are also characterized by the presence of a band gap.…”
Section: Resultsmentioning
confidence: 84%
“…Indeed, following the SEP definition 2 given in the introduction and our previous works, [17,18] the surface contribution, K S , to the inelastic crosssection is…”
Section: Theoretical Model and Sep Resultsmentioning
confidence: 99%
“…[16] That implies that SEP obtained within this definition cannot be directly used as a correction factor to the elastic peak intensity (on the form exp[−P s (E, θ )]), but this is nevertheless what is done by Zemek et al, [11] for example. This complication is overcome with an approach introduced in our previous works [17,18] by redefining the surface excitation parameter as -SEP definition 2: The SEP is the change in excitation probability, for an electron, caused by the presence of the surface in comparison with the situation where the electron travels the same distance in an infinite medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is especially pronounced at low electron energies and oblique emission angles and, particularly, in the techniques that use primary electron beams for electron spectra excitation, where an electron passes the surface twice. [56][57][58][59][60] Note that the corrections for surface inelastic losses can be easily added in the intensity matrix Iijk in Eq. (12).…”
Section: ·5 Semi-empirical Methodsmentioning
confidence: 99%